2008
DOI: 10.1002/j.2333-8504.2008.tb02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking English‐language Test Scores Onto the Common European Framework of Reference: An Application of Standard‐setting Methodology

Abstract: The Common European Framework of Reference (CEFR) describes language proficiency in reading, writing, speaking, and listening on a 6-level scale. In this study, English-language experts from across Europe linked CEFR levels to scores on three tests: the TOEFL ® iBT test, the TOEIC ® assessment, and the TOEIC Bridge™ test. Standard-setting methodology (a modified Angoff approach and a modified examinee paper selection approach) was used to construct the linkages. Linkages were established for TOEFL iBT at level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…During a standard setting study, expert panelists are asked to make judgments about the performance of examinees with varied ability (as indicated by the CEFR performance descriptors) on test items. The outcome of such studies is a minimum test score that an examinee needs to achieve to be classified as minimally able to perform language tasks described at each CEFR level (see, e.g., Papageorgiou, 2010c;Tannenbaum & Wylie, 2008). Although the standard setting approach is largely subjective, empirical test performance data are also used to help panelists make their judgments and validate the cut scores.…”
Section: Developing and Validating Band Levels And Descriptors For Rementioning
confidence: 99%
See 1 more Smart Citation
“…During a standard setting study, expert panelists are asked to make judgments about the performance of examinees with varied ability (as indicated by the CEFR performance descriptors) on test items. The outcome of such studies is a minimum test score that an examinee needs to achieve to be classified as minimally able to perform language tasks described at each CEFR level (see, e.g., Papageorgiou, 2010c;Tannenbaum & Wylie, 2008). Although the standard setting approach is largely subjective, empirical test performance data are also used to help panelists make their judgments and validate the cut scores.…”
Section: Developing and Validating Band Levels And Descriptors For Rementioning
confidence: 99%
“…Language test providers typically refer to the six main proficiency levels (A1-C2) of the CEFR to help score users interpret the meaning of test scores (Papageorgiou, 2010b;Tannenbaum & Wylie, 2008;Taylor & Jones, 2006). It has been argued that this use of the CEFR levels can be helpful in assisting users with score interpretation.…”
Section: Developing and Validating Band Levels And Descriptors For Rementioning
confidence: 99%
“…The proficiency level of the target learners for the course is estimated to be somewhere between A2 and B1. This estimate is based on Tannenbaum and Wylie (2008). They show that the cut-scores of TOEFL and TOEIC 3 correspond to levels A1 through C1 of the CEFR.…”
Section: Selection Of Cefr Descriptors For a Remedial Reading Coursementioning
confidence: 99%
“…All participants had received at least seven years of high school and university-level English instruction at the time of the study, and the majority of the participants were required to take two English courses designed to improve their receptive and productive skills. Based on their TOEIC speaking test scores (M = 134.6; SD = 19.0), the speaking proficiency levels of most participants were B1 (72.2%) and A2 (16.7%), according to the Common European Framework of Reference for Languages (Tannenbaum & Wylie, 2008). Their TOEIC LR test scores (M = 767.2; SD = 115.1) showed that their receptive skills mainly belonged to B1 (51.8%) and B2 (37.0%) levels.…”
Section: Participantsmentioning
confidence: 99%